Contribution of pyrolytic gas medium to the fabrication of co-impregnated biochar. (July 2018) - Cho, Dong-Wan; Kim, Sohyun; Tsang, Daniel C.W.; Bolan, Nanthi S.; Kim, Taejin; Kwon, Eilhann E.; Ok, Yong Sik; Song, Hocheol
Graphical abstract: Highlights: Pyroylsis of glucose and spent coffee grounds under N2 and CO2 . Physicochemical characteristics of biochar varying with pyrolytic gas medium. Catalytic capability of biochar closely correlated with its external surface. Demonstrated significance of pyrolytic gas medium for cobalt-biochar fabrication. Abstract: Co-impregnated biochars were fabricated by pyrolysis of spent coffee grounds (SCG) or glucose as carbon (C) sources under N2 and CO2 . The formed biochar samples were characterized with FE-SEM, TEM/EDS, XRD, TGA, Raman, XPS, and BET, and further used as catalytic medium for the reduction of p -nitrophenol in the presence of NaBH4 . The physicochemical characteristics of biochar significantly changed with the types of C precursor and flow gas stream. The biochar from pyrolysis of SCG under N2 gas stream showed good dispersion of Co nanoparticles (10–20 nm) in carbon matrix as compared to that produced under CO2 stream, but BET surface area was very small (4.5 m 2 g −1 ) due to pore blockage by thermal degradation products. SCG-derived biochar formed in the presence of CO2 possessed highly porous structure due to CO2 -assisted C volatilization. In contrast, for glucose-derived biochar, significant reduction in porosity of biochar occurred with excess devolatilization of C under CO2 conditions, while the pyrolysis under N2 flow produced porous biochar. These contrasting results demonstrated the significance of structure crystallinity and thermal degradability of C precursors. The catalytic performance of biochar was better correlated with the external surface area rather than microporosity.